The association of urinary tract infection with urothelial carcinoma - Abdul-Lateef, Yasir M. (Iraqi Journal of Cancer and Medical Genetics, 2015)
Background: In Iraq bladder carcinoma is a major problem according to the results of the Iraqi cancer registry between the years (1991-2006). Cancer of the urinary bladder was the 2nd on the table of the commonest ten cancers in male and it was the 8th commonest cancer in females (1). According to the same registry the main histological types were: Transitional cell carcinoma: 43.82%. Sequamous cell carcinoma: 4.49%. Undifferentiated cell carcinoma: 0.31 %. Adenocarcinoma: 0.92%. Male to female ratio was 3.39:1 the peak age incidence was found in the 70+ years (1). Bilharzial ovals were found in about 7%-29% of bladder cancers, which is lower than that in Egypt; 82-90% (2). On the other hand urinary tract infections are among the most common bacterial infections that lead patients to seek medical care. It had been estimated that more than 6 million outpatient visits and 300,000 hospital stays every year are due to urinary tract infections (3). The aim of this study is to find the association or disassociation between bacterial infection of the urothelium and urothelial carcinoma and if it was associated which type is it: causative or associative. Material and Method: This study was carried out on 105 patients with carcinoma of the bladder (transitional, sequamous), whom were referred to the surgical specialties hospital, medical city for diagnostic transurethral endoscopy during the period between 5th of October 2007 till the 1st of September 2008. History of smoking, previous recurrent urinary tract infection and stone was taken, identification of the causative bacteria for their urinary tract infection was done from three samples collected; two urine samples (on admission and post-operatively) and one tissue sample (tumor biopsy). Results: The results showed that: 85.65% of the patients had infections associated with their tumors, the rest 14.35% were negative. These infections were either Escherichia coli, Klebsiella, Proteus, Staphylococcus, Enterobacter, Citrobacter or Morganella spp. Escherichia coli was the most common 73.3% of all the cases. The results also showed that there was a significant association between positive urine culture on diagnosis for bacterial growth and urothelial carcinoma, also Escherichia coli was collected from the intracellular compartment by a mechanical approach. Conclusion: Associations between urothelial carcinomas and bacterial growths were studied and showed that urothelial carcinomas were highly associated with bacterial growth especially Escherichia coli. Although Klebsiella, Proteus, Staphylococcus, Enterobacter, Citrobacter or Morganella spp., occured in a lower incidence, still had a role in urinary tract infection. Finding Escherichia coli intracellular and its high association with urothelial carcinoma could put these bacteria in the causative section of urothelial carcinoma through producing a recurrent acute infection.